Standardisation of Microencapsulation Protocol for Cryopreservation of Malabari Goat Semen - George, Kiran Mariya; Becha, Bahuleyan Bibin; Unnikrishnan, Melitta Pappu; Jayakumar, Choppillil; Nair, Suresh Narayanan; Chandrasekhar, Leena (The Indian Journal of Animal Reproduction, 2025)
The study was conducted to characterise fresh semen and to standardise a microencapsulation protocol for cryopreser vation of Malabari buck spermatozoa. Fresh semen evaluation revealed the ejaculate volume (1.10 ± 0.24 ml), progressive motility (87.50 ± 2.14 %), concentration of spermatozoa (3829.16 ± 172.01 million/mL), viability (92.16 ± 1.62 %), mor phological abnormalities (1.91 ± 0.23 %), functional membrane integrity (64.00 ± 1.93 %) and acrosome integrity (93.16 ± 1.01 %) within normal range. Pooled good quality ejaculates from bucks with good semen freezability were extended in Tris egg yolk based extender; microcapsules were prepared after mixing with sodium alginate at different concentra tions (2.5% and 3%), at different ratios of alginate and extended semen (1:0.6 and 1:1) and extruding through different sizes of hypodermic needle (22 G, 23 G and 24 G) to obtain microcapsules of different size and shape. The size, shape and wall integrity of microcapsules were evaluated in all combinations of production parameters. Alginate concentration of 3 per cent, when mixed with extended semen at the ratio 1:1 and extruded through a 24 G needle into a five per cent barium chloride solution at a fixed distance of 3 cm from the needle tip yielded globular, 1.7 mm sized capsules with 65 per cent wall integrity.
Keywords: Semen evaluation; Microencapsulation; Alginate; Microcapsule; Malabari; Goat